Cross-sectional average length of life by parity: Country comparisons - Mogi Ryohei; Lazzari Ester; Nisen Jessica; Canudas-Romo Vladimis (Taylor & Francis, 2022)
This study aims to present an alternative measure of fertility—cross-sectional average length of life by parity (CALP)—which: (1) is a period fertility indicator using all available cohort information; (2) captures the dynamics of parity transitions; and (3) links information on fertility quantum and timing together as part of a single phenomenon. Using data from the Human Fertility Database, we calculate CALP for 12 countries in the Global North. Our results show that women spend the longest time at parity zero on average, and in countries where women spend comparatively longer time at parity zero, they spend fewer years at parities one and two. The analysis is extended by decomposing the differences in CALPs between Sweden and the United States, revealing age- and cohort-specific contributions to population-level differences in parity-specific fertility patterns. The decomposition illustrates how high teenage fertility in the United States dominates the differences between these two countries in the time spent at different parities.